Description of Mothers' Knowledge About Nutritional Status in Toddlers at Baamang I Community Health Center, Kotawaringin Timur Regency, Central Kalimantan Province - Norwidya Priansiska; Maya Yulia Handayani; Aulia Ridla Fauzi (Genius Midwifery Journal, 2023)
Introductions: Nutritional status is a state of the body that is influenced by certain nutrients as a result of food consumption. The factors of age, education, and occupation are some of the factors that influence the knowledge of mothers under five regarding the nutritional status of children under five. Objectives: To describe the factors that influence the knowledge of mothers under five about the nutritional status of children under five at the Baamang I Public Health Center in 2022. Methods: This study uses quantitative methods. It was conducted at the Baamang I Sampit Health Center in June 2022 with a sample of 30 people using the Accidental Sampling technique from secondary and primary data single variable. Results: The knowledge factor of mothers under five regarding the nutritional status of toddlers with the majority aged 20-35 years as many as 7 people, the majority of Diploma and Bachelor education as many as 5 people, the majority work with mothers who do not work as many as 4 people. The factor is sufficient knowledge of mothers under five regarding the nutritional status of toddlers with the majority aged >35 years as many as 11 people, the majority of high school / vocational education being 13 people, the majority working with mothers who do not work as many as 11 people and also the factor of lack of knowledge of mothers under five regarding nutritional status in toddlers with the majority aged >35 years as many as 6 people, the majority of elementary and junior high school education being 8 people, the majority working with mothers who do not work as many as 6 people. Conclusions: The results of the univariate and bivariate analysis of 30 respondents that there is a description of the age factor that age affects the knowledge of mothers under five about nutritional status in toddlers and educational factors affect mother's knowledge about nutritional status in toddlers and also occupational factors affect the knowledge of mothers under five about nutritional status in children under five toddler.